2002
DOI: 10.1002/hed.10039
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal integration of Epstein ‐ Barr virus genomes in nasopharyngeal carcinoma cells

Abstract: This is the first in vitro model of EBV persistence in NPC cells by genomic integration, which represents a unique state of virus-cell interaction. Using this model, investigation into the association between EBV integration and chromosomal abnormality in tumor cells will help to reveal the underlying biologic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The EBV lytic program results in inhibition of host cellular DNA replication and disruption of DNA repair, leading to accumulation of unrepaired DNA and consequent genomic instability 36. Cytogenetic studies have suggested that genomic instability may be a common feature in the development of NPC 37–40. As HHR pathway proteins appear to play an important role in lytic reactivation of EBV virus, we hypothesized that the genes coding proteins involved in lytic reactivation of virus may influence seropositivity rates.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV lytic program results in inhibition of host cellular DNA replication and disruption of DNA repair, leading to accumulation of unrepaired DNA and consequent genomic instability 36. Cytogenetic studies have suggested that genomic instability may be a common feature in the development of NPC 37–40. As HHR pathway proteins appear to play an important role in lytic reactivation of EBV virus, we hypothesized that the genes coding proteins involved in lytic reactivation of virus may influence seropositivity rates.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed and digested by proteinase K as described previously and then subjected to the following PCR analysis (Chang et al, 2002). Conventional PCR detection of BamHI W fragments of the EBV genome was performed following our previous protocol (Chang et al, 2002). For quantification of EBV DNA, real-time PCR was used according to the manufacturer's instructions (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…H2B4 cell, a nasopharyngeal carcinoma cell clone harboring one copy of the EBV genome was used as a positive control (14). In our series, once the PBMC EBV viral load above 100 copies/g PBMC DNA was noted, we rechecked the viral load 2 weeks later.…”
Section: Quantification Of Ebv Dna Viral Load In Peripheral Blood Monmentioning
confidence: 99%